Core Strength Training Terhadap Perubahan Nyeri dan Activity Daily Living Pada Penderita Low Back Pain - Meutiah Mutmainnah Abdullah; Riskah Nur’amalia; Winda Mey Zulvina; Zein Mauludil Adhim; Herdin Herdin (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Low Back Pain (LBP) is a complaint often found in the community; it is a problem in the community because it often results in sufferers being disturbed or unable to carry out daily tasks. Objective: Knowing the effect of Core Strength Training (CST) on changes in pain and daily living (ADL) activities in patients with low back pain (LBP). Method: This study is quasi-experimental with a pretest-posttest one-group design study where the effect of exercise is measured before and after treatment. The sample was 15 people consisting of 53.5% women and 46.7% men with an age range of 25-65 years. Results: Statistical tests using the Wilcoxon test obtained a significant value of p = 0.001 (p<0.05), which showed that there were substantial changes before and after the administration of Core Strengthening Training by looking at a decrease in pain and an increase in Activity Daily Living (ADL) in Low Back Pain patients. Conclusion: There is a decrease in pain and an increase in Activity Daily Living (ADL) after the administration of Core Strength Training in LBP patients.